Peddling prosperity : economic sense and nonsense in the age of diminished expectations - Krugman, Paul R. (New York : W.W. Norton, 1994)
The past twenty years have been an era of economic disappointment in the United States. They have also been a time of intense economic debate, as rival ideologies contend for policy influence. Above all, they have been the age of the policy entrepreneur -the economic snake-oil salesman, right or left, who offers easy answers to hard problems. It started with the conservative economists - Milton Friedman at their head - who made powerful arguments against activist government that had liberals on the defensive for many years. Yet when Ronald Reagan brought conservatism to power, it was in the name not of serious thinkers but of the supply-siders, whose ideas were cartoon-like in their simplicity. And when the dust settled, it was clear that the supply-side treatment not only had cured nothing, but had left behind a $3 trillion bill.
Meanwhile, the intellectual pendulum had swung. In the 1980s, even while conservatives ruled in Washington, economic ideas that justified government activism were experiencing a strong revival. But the liberals, it turns out, have their own supply-siders: the strategic traders, whose simplistic vision of a U.S. economy locked in win-lose competition with other countries proved far more appealing to politicians than less-dramatic truth.
Includes bibliographical references and index.
Keywords: Keynesian economics; Supply-side economics; Economics -- Political aspects